Evolutionary Sequences and Structural Information-driven Reconstruction of New Insulin-like Growth Factor-I Peptide Variants - Khan, Nazam; Althobiti, Maryam; Chinnadurai, Raj Kumar; Alharbi, Samir; Kumar, Rajender (Current Molecular Medicine, 2025)
BackgroundInsulin-like growth factor-I (IGF-I) is crucial in controlling cell growth, proliferation, and apoptosis. Its strong link to the development of cancers such as breast, prostate, lung, thyroid, and colorectal has positioned the IGF-1 signalling pathway as a promising target for novel cancer therapies. When activated, the IGF-1 receptor (IGF-1R) binds to IGF-I, playing a central role in promoting tumour cell growth and survival.MethodsIn this study, we combined evolutionary sequences with structural and functional data of IGF-1 to reconstruct ancestral sequences and design novel IGF-1 peptide variants.ResultsThe insulin-like growth factor system exhibits a vast sequence diversity, yet it shares a similar structural topology with conserved three pairs of disulfide linkages. Our study reveals that IGF-1 is associated with the IGF system of cell surface receptors through protein-protein interactions. Reconstructed IGF-1 variants show similar structure fold to reported viral IGF-1 competitive antagonists.ConclusionThis new insight guides the design of novel natural IGF-1 mimic peptides. It enhances our understanding of IGF-1's functionality and opens new avenues for the development of therapeutic peptides and small molecules as anti-cancer agents.
Keywords: IGF-IR